EFFORT OF THE LECTURES TO IMPROVING ENGLISH SKILLS IN INTENSIVE COURSE CLASS - Usman, Safinatun Najah; Ismiatun, Febti; Ashari, Ali (Journal of English Educational Study (JEES), 2025)
ICT plays an important role in all aspects of daily life, especially in teaching and learning. The purpose of this study is to find out the efforts of lecturers in improving English language skills in intensive course classes. The research uses a qualitative method with a single case study design. The participants in this study were taken 2 participants from private university lecturers’ who taught intensive course classes in the first semester. The results of this study show that lecturers make various efforts to improve students' English language skills in the Intensive Course class, in response to the challenges faced in the class. The efforts and strategies made by lecturers include: (1) utilizing students with good English skills, (2) providing additional time outside of class hours, (3) supporting the formation of study clubs among classmates, (4) providing directions for utilizing technology or artificial intelligence (AI), and (5) motivating students to stay enthusiastic.